ADVANCED MACHINE TOOLS: HOW BEST TO TRAIN OPERATORS - Thummalapalli, Rama; Yeddula, Vineeth R; Musunuru, Vijaya K; Jones, Erick C; Bishu, Ram (International Journal of Industrial Engineering: Theory, Applications and Practice, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Modern machine tools are very intelligent and capable of fine levels of adaptive control. Without proper training, the ability to operate these machine tools is difficult and critical in operator’s day to day schedule. A mental model developed by the operator’s to understand the work flow can be simplified for the better understanding of the work flow with training. With the developments in the current technology, computer based interactive training seems to be the future and effective way for organizations. A relevant issue is the question of displaying the image appropriately on the computer screen, so that operator control action is facilitated /learned has been discussed briefly. The purpose of this study was to compare different training methodologies assisting the operators and equip them with new set of skills to improve work efficiency. The results from the comparison have been discussed by implementing training procedure on two machines to train the operators in handling the machine. A detailed comparison methodology has been illustrated. The results indicate that training using simulation methods are the best in all measures of performance. However, experienced operators preferred traditional methods compared to computer based methods. More research is needed for generalizing the findings.